Moderat Antar Umat, Pendidikan, dan Organisasi di Indonesia - Tatang Muh Nasir; Opik Taufik Kurahman (Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2023)
The moderate stance taken by religious, educational and organizational groups is discussed in this article. This study used a literature review, and moderate was defined either explicitly or implicitly. The word